Popioły Marci Shore - Kopeć, Zbigniew (My University, 2013)
The article discusses Marci Shore’s social and historical thought, as presented in her books: "Caviar and Ashes: A Warsaw Generation’s Life and Death in Marxism, 1918-1968" (2006), "The Taste of Ashes" (2013), and her essays recently published in Polish translation. The author follows the American historian, presenting her concept of modernity, but focuses on the main theme of her research: the contribution of Jewish writers, poets, artists, and intellectuals to the creation of Marxism. The author acknowledges the great value of Marci Shore’s writings, but argues that her panorama of the 20th century would be fuller if her discussion included a reflection on the religious attitude of many Jewish thinkers to Marxism and the USSR. This topic was discussed by Nikolai Berdyaev and Polish thinkers who published in pre-war social journals.
The Ashes of Marci Shore
Keywords: avantgarde; Jewish culture; Marxism; history; Eastern Europe; Communism